2019
DOI: 10.3390/ma12132174
|View full text |Cite
|
Sign up to set email alerts
|

Machinability of Luxury Vinyl Tiles during Plain Milling Using a Helical Cutter

Abstract: In order to better provide a theoretical basis for the machining of luxury vinyl tiles, a helical milling experiment was conducted by using diamond cutting tools, and special attention was given to the trends of cutting force and surface roughness in respect to tool geometry and cutting parameters. The results showed that the resultant force was negatively correlated to the helix angle and cutting speed, but positively correlated with the cutting depth. Then, that the surface roughness increased with a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The complete reverse (opposite) process is the modeling of the material separation. In this case, the process should be designed in such a way that the Huber–Mises reduced stress should exceed the allowable stress that appears in the direct cutting zone [5,6,7,8,9,10,11]. Otherwise, the material being removed would not be separated.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete reverse (opposite) process is the modeling of the material separation. In this case, the process should be designed in such a way that the Huber–Mises reduced stress should exceed the allowable stress that appears in the direct cutting zone [5,6,7,8,9,10,11]. Otherwise, the material being removed would not be separated.…”
Section: State Of the Artmentioning
confidence: 99%
“…Nowadays, the works concerning the numerical modelling of machining processes using FEM (the finite element method) are very popular. Many literature positions describe numerical or experimental investigations of machining processes, such as turning [5], milling [6,7,8], boring [9,10], grinding [11], etc. Much less attention is given to covering mechanical cutting on guillotines [12,13,14,15,16,17,18].…”
Section: State Of the Artmentioning
confidence: 99%
“…In addition, tool related parameters also influence the processing energy consumption and different tool structures require different cutting powers [32]. Studies have shown that helical cutters have stronger cutting stability and higher surface quality than straight cutters [33–35]. The influence of helical cutters and straight cutters on the cutting power during the processing of maple sugar wood was studied, and it was found that helical cutters required less cutting power than straight cutters [36].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, as the cutting speed increases, the cutting force gradually decreases, and on the other hand, the increase of the feed speed always led to a higher cutting force. Zhu et al 18 investigated the relationship between cutting force and helix angle, cutting speed, and depth of cut when milling Luxury Vinyl Tiles.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, milling is also a research focus in the field of material processing. 24 Compared with a straight-tooth cylindrical milling cutter, using a helical-tooth milling cutter 18,25,26 to mill the workpiece is not only stable, less vibration, but also improves the processing quality and reduces noise.…”
Section: Introductionmentioning
confidence: 99%